Paradoxical response of prostate cancer skeletal metastases to androgen deprivation therapy - Wosnitzer, Brian (Elsevier, 2015)
We report a marked geographically inconsistent response of prostate cancer skeletal metastases to androgen deprivation therapy. Such inconsistent response to therapy has not been described previously in the literature and should be correlated with individual patient history. Further understanding of the mechanism of geographic responses to hormone deprivation therapy may have implications in the targeting of specific regions of disease for treatment in the future.